2009
DOI: 10.1523/jneurosci.3044-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Endolymphatic Sodium Homeostasis by Extramacular Epithelium of the Saccule

Abstract: The saccule is a vestibular sensory organ that depends upon regulation of its luminal fluid, endolymph, for normal transduction of linear acceleration into afferent neural transmission. Previous studies suggested that endolymph in the saccule was merely derived from cochlear endolymph. We developed and used a preparation of isolated mouse saccule to measure transepithelial currents from the extramacular epithelium with a current density probe. The direction and pharmacology of transepithelial current was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…In addition, Pisam et al [1998] identified what they termed a "patches area" in the roof of the saccular chamber with cellular morphologies suggestive of secretory activity, but heterogeneous across the different teleost species (trout and turbot). The location of their "patches area" is consistent with what has been termed the "extramacular epithelium" of the sacculus in mammals [Kim and Marcus, 2009].…”
Section: Evolution Of the Inner Ear Endolymphatic Systemsupporting
confidence: 67%
“…In addition, Pisam et al [1998] identified what they termed a "patches area" in the roof of the saccular chamber with cellular morphologies suggestive of secretory activity, but heterogeneous across the different teleost species (trout and turbot). The location of their "patches area" is consistent with what has been termed the "extramacular epithelium" of the sacculus in mammals [Kim and Marcus, 2009].…”
Section: Evolution Of the Inner Ear Endolymphatic Systemsupporting
confidence: 67%
“…ENaC is involved in fluid transport in the inner ear, being important for maintaining a much lower sodium concentration in the endolymph in the saccule (220,221), and the semicircular canals (310,311), as compared with that in the perilymph. These findings are of relevance for conditions such as Meniere's disease, where an increased volume of endolymph underlies the dysregulation of balance and symptoms of vertigo experienced by those afflicted.…”
Section: Enac In the Peripheral And Central Nervous Systems And In Sementioning
confidence: 99%
“…ENaC was identified in the semicircular canal duct (Pondugula et al, 2006) and non-sensorycells of the extramacular epithelium of the saccul e (Kim and Marcus, 2009). Na + ,K + -ATPase was found in the basolateral surface of semicircular canal duct epithelial cells (α 1 -, α 3 -, β 1 - and β 3 -isoforms) (Pondugula et al, 2006; Pondugula et al, 2004), extramacular epithelium of the saccule (Kim and Marcus, 2009), vestibular dark cells (α 1 -and β 2 -isoforms) (McGuirt and Schulte, 1994), and vestibular transitional cells (α 1 -and β 1 -isoforms) (McGuirt and Schulte, 1994). NKCC1 was found in the basolateral membrane of vestibular dark cells and cellular membrane of transitional cells (Young et al, 2005).…”
Section: Vestibular Systemmentioning
confidence: 99%